Estudo piloto empregando curcumina fotoativada com luz azul no tratamento da acne facial graus i e ii - Simão, Gabriely (Universidade Federal de São Carlos, 2025)
Acne vulgaris is a chronic inflammatory condition of the pilosebaceous unit that significantly impacts the quality of life of young adults. Photodynamic therapy (PDT) has emerged as a promising alternative to conventional treatments due to its localized action and lower risk of systemic side effects. This study evaluated the efficacy of PDT using 1.5% curcumin activated by blue light (465 ± 10 nm) for the treatment of grade I and II acne through in vitro and in vivo approaches. In the in vitro stage, Cutibacterium acnes strains were exposed to different concentrations of curcumin, with or without irradiation, and assessed by spectrophotometry (OD600) and optical fluorescence. The combination of curcumin and blue light significantly reduced bacterial viability (p < 0.001), confirming its photosensitizing action. In the in vivo stage, 16 volunteers (aged 25–35) were divided into four groups: control, blue light, curcumin, and PDT. The protocol consisted of 16 sessions over 60 days. Objective evaluations included skin hydration and oiliness (Skin Analyser®), porphyrin fluorescence (EVINCE®), and standardized photographic records. In the PDT group, a significant reduction in red fluorescence intensity was observed between the 1st, 8th, and 16th sessions (glabella: 6.72 ± 1.02 → 3.81 ± 0.84; p < 0.001), indicating decreased bacterial activity. Skin oiliness also significantly decreased (glabella: 58.7 ± 7.4 → 42.3 ± 5.6; p < 0.05), with similar trends in malar and mentonian regions. Although hydration did not differ significantly, a trend toward improvement was noted in the PDT group. Clinically, visible regression of inflammatory lesions was observed, especially after the 8th session. It is concluded that PDT with 1.5% curcumin activated by blue light demonstrates significant antimicrobial and anti-inflammatory effects, representing a safe, effective, and minimally invasive alternative for the treatment of grade I and II acne.
Pilot study using photoactivated curcumin with blue light in the treatment of grade i and ii facial acne
Keywords: Acne; Pele; Curcumina; Terapia Fotodinâmica; LEDs; Skin; Antimicrobial Photodynamic Therapy; Curcumin; Blue LED; CIENCIAS DA SAUDE; 3. Saúde e Bem-Estar